Preventive medicine and community health: al-Maqasid approach - Bendebka, Ramzi; Shogar, Ibrahim; Fettane, Amar (2019)
Incorporating maqasid al-Sharī’ah approach, this poster aims to highlight the potential role of preventive medicine in promoting health within the community, using maqasid al-Sharī’ah. So far, the literature on maqasid al-Sharī’ah focuses on developing the theory and defining the dimensions of that approach. The application of the approach in various medicine, health, community and social aspects started recently. This study tries to apply maqasid al-Sharī’ah framework to identify the role of preventive medicine in community health. Therefore, this poster proposes that preventive medicine from an Islamic view must be based on the five principle objective of Islamic law (Maqasid al-Shari`ah) which are also considered the five purposes of preventive medicine.